The Sources and Effects of Retirement Planning: An Empirical Study of Sandwich-Generation Employees in Indonesia - Maria Rio Rita; Yeterina Widi Nugrahanti; Pambayun Kinasih Yekti Nastiti (Media Ekonomi dan Manajemen, 2024)
This research aims to analyze the retirement planning of employees belonging to the sandwich generation by considering financial literacy, collectivist culture, and family financial responsibility that promote financial and psychological well-being. We run the SEM-PLS to analyze the data from 200 sandwich-generation employees between 25-55 years old. The results demonstrate that financial literacy positively affects financial and psychological well-being, collectivist culture positively affects family financial responsibility, family financial responsibility affects retirement planning and psychological well-being, as well as retirement planning positively affects financial and psychological well-being. These findings indicate that personal and financial factors contribute to retirement planning for sandwich generation employees. It is hoped that planning for retirement early can break the chain of births of the next sandwich generation in the family, so that financial and psychological well-being can be achieved. This paper implies that sandwich-generation employees must plan their retirements early and wisely to achieve financial well-being and even break the chain of the next sandwich-generation.